Case Report: Large nested variant urothelial carcinoma –invasive malignancy masquerading as low grade disease [v1; ref status: indexed, http://f1000r.es/4xb] - Andrew Keller; Ai Jye Lim; Ahmad Ali (F1000Research, 2014)
Introduction The large nested variant of urothelial carcinoma (LNVUC) is a newly described and rare subtype of urothelial carcinoma. It is characterised by bland cytological features and a large nested architecture similar in appearance to low grade urothelial carcinoma with an inverted growth pattern. To date only 23 cases in a single series have been described.   Case Report We describe the case of a 59 year old male with LNVUC whose tumour was initially misdiagnosed as a non-invasive low grade urothelial carcinoma. At a subsequent re-resection, his tumour was correctly re-classified as LNVUC with extensive invasion of the muscularis propria. Radical cystectomy and formation of an ileal conduit was performed. His operative specimen revealed invasion of prostatic stroma and perivesical fat, with all surgical margins clear. He is currently free from clinical recurrence 12 months after his cystectomy.   Conclusion LNVUC is a newly described and rare urothelial carcinoma subtype. It characteristically possesses bland cytological features and may mimic low grade urothelial cancer. Despite its bland appearance it behaves aggressively with invasion, metastasis and death being common.